The nature and scope of lawyers' liability for the negligent rendering of professional services - Midgley, John Robert (Department of Private Law, 2026)
The thesis covers the field of law also known as professional negligence. It deals with three major areas of uncertainty. The first is whether South African lawyers should receive protection from' suit-similar to that which their counterparts in some Commonwealth countries currently enjoy. An analysis of the justifications for immunity from suit and a comparision of relevant principles in South Africa and in the countries which grant protection to lawyers indicate that immunity is not a suitable form of protection. General principles of contractual and delictual liability should apply to lawyers. However, where lawyers can show that their conduct was pursuant to the proper administration of justice such conduct should be protected: policy dictates that contractual obligations should not be enforced, while in delict the conduct is not wrongful. The second area which is focussed upon is the foundation of lawyers' liability and whether lawyers are liable to clients concurrently in contract and in delict. The conclusion reached is that clients should have a choice of actions. In relation to the first two topics, a distinction is drawn between enquiries in which policy considerations prevent the application of substantive contractual and delictual principles and those in which public policy is considered in terms of the laws of contract and delict. Questions of concurrence of liability and protection from suit are placed in the former category. The third major topic is the question of liability to persons who are not clients. Whether it is possibe to extend contractual or delictual principles to third party situations, and the criteria to be considered in doing so, are discussed. It is concluded that delictual liability is possible in circumstances where the lawyer has knowledge of the extent to which his or her conduct is intended to affect the plaintiff, but no liability arises where the conduct accords with ethical duties, nor where any potential duty to a non-client conflicts with the lawyer's duty to a client. In addition to the above topics, general principles of lawyers' liability are set out and consideration is given to methods of reducing the risks attached to the practice of law.